Development of National Production Base in the Context of the Implementation of New Economic Policy - Vladimir KOVARDA; Roman LAPTEV (Communications of International Proceedings, 2020)
The social, political and economic development of Russia in the 1920s was largely determined by the legacy of the Civil War and War Communism. Historians discuss the importance of the NEP (New Economic Policy) phenomenon, which is an extremely unyielding subject of research for a number of reasons.
Keywords: New Economic Policy; government investment; War Communism; Civil War; cooperative economy management.